Analysis of Factors Causing Errors in Issue of Goods at PT Dunia Express Transindo's Warehouse - Edwar Rosyidi; Nensi Yuselin; Kamil Yahya (Jurnal Syntax Transformation, 2023)
PT Dunia Express Transindo is a "Total Logistics" service provider company. One of the services provided is the warehouse division to manage all the activities in it, starting from the process of Inbound / Receiving goods, Storage / Storage of goods, and Outbound / Issuing goods. In the process, there were problems found in the warehouse, namely an error in the Outbound process /Releasing goods in the warehouse, which resulted in an internal impact for the company, namely an error in releasing goods causing re-shipment to customers. Also the external impact on the company, namely errors in issuing goods causes the level of customer trust to decrease. Data collection was carried out by asking directly to the field workers (warehouse staff and warehouse coordinator) and directly observing the condition of the warehouse. This study retrieved data on errors in the issuance of goods in December 2020 with a total of 13 items and January 2021 with a total of 96 items. From the root of the problem using the fishbone diagram method and cause and effect. It is known that the human factor is the most dominant factor due to lack of thoroughness, lack of knowledge and lack of communication. After carrying out an analysis of the repair plan using the 5w1h method, the DUNEX Wms Dry application was implemented and the socialization was carried out during the morning briefing. So that it can reduce errors in issuing goods, speed up reporting the previous process from 2 hours to 5 minutes, report damage to the previous 30 minutes to 3 minutes and make it easier to find out which items have been collected.